IMPROVING AUDIT EVIDENCE AND ITS COLLECTION METHODS - Mamatov Khabibulla Mamatovich,; Avlayeva Oybarchin, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article provides information on the essence, types and sources of audit evidance, obtaining audit evidance and factors that can affect the quality of audit evidence. The use of internal and external sources, their reliability, relevance and importance in collecting audit evidence are indicated. Also, the reliability of audit evidence is increased when it is obtained from independent sources, the effectiveness of internal control measures and its advantages compared to documentary evidence.